2020
DOI: 10.1097/acm.0000000000003382
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between the USMLE Step Examinations, American College of Physicians In-Training Examination, and ABIM Internal Medicine Certification Examination

Abstract: Purpose To assess the correlations between United States Medical Licensing Examination (USMLE) performance, American College of Physicians Internal Medicine In-Training Examination (IM-ITE) performance, American Board of Internal Medicine Internal Medicine Certification Exam (IM-CE) performance, and other medical knowledge and demographic variables. Method The study included 9,676 postgraduate year (PGY)-1, 11,424 PGY-2, and 10,239 PGY-3 internal medici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 43 publications
4
40
0
Order By: Relevance
“…These findings are consistent with reports from other internal medicine subspecialties showing that ITEs and prior standardized testing performance also predict outcomes on their respective subspecialty certification examinations [ 4-9 ]. Younger age on date of ABIM-ECE was the only other significant predictor, and this result also mirrors prior studies that found younger test-takers were more likely to pass initial board certification examinations on the first attempt [ 3 , 7 , 22 ]. Although reasons for this are speculative, Jeffe and Andriole have suggested that such results indicate older graduates may experience greater difficulties in timely advancement toward board certification [ 22 ].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These findings are consistent with reports from other internal medicine subspecialties showing that ITEs and prior standardized testing performance also predict outcomes on their respective subspecialty certification examinations [ 4-9 ]. Younger age on date of ABIM-ECE was the only other significant predictor, and this result also mirrors prior studies that found younger test-takers were more likely to pass initial board certification examinations on the first attempt [ 3 , 7 , 22 ]. Although reasons for this are speculative, Jeffe and Andriole have suggested that such results indicate older graduates may experience greater difficulties in timely advancement toward board certification [ 22 ].…”
Section: Discussionsupporting
confidence: 82%
“…When used as intended, the ESAP-ITE represents an important resource for assessment of medical knowledge and self-identification of potential knowledge gaps. McDonald et al have shown that “a systematic, frequent (eg, daily), modest (eg, ≤20 minutes per day), intentional approach to medical knowledge acquisition” is associated with significant gains in knowledge over time [ 3 , 23 ]. Such an approach, when guided by ESAP-ITE results, could conceivably increase odds of an “at-risk” test-taker passing the ABIM-ECE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IM-ITE has been demonstrated to correlate with rate and degree of knowledge acquisition during residency 13 and predicts performance on the American Board of Internal Medicine Certification Examination (IM-CE). [14][15][16] Furthermore, higher performance on the IM-CE has been associated with better patient care outcomes. [17][18][19] Studies have demonstrated that TBL in undergraduate medical education can lead to improvements in students' subject area standardized testing performance.…”
Section: Discussionmentioning
confidence: 99%
“…Once the Accreditation Council of Graduate Medicine Education’s Next Accreditation System (ACGME-NAS) was implemented in July 2014, a new continuing accreditation metric requiring a program to achieve and maintain a recent, rolling 3-year first attempt pass rate of >80% on the ABIM-CE by their graduates[ 1 ] likely led to a proliferation and increased use of such online tools. The IM-ITE performance has been correlated with passing the ABIM-CE and such supplemental use for remediation has successfully been reported [ 2 ].…”
Section: Introductionmentioning
confidence: 99%